FOREIGN ECONOMIC SANCTIONS ON COMMERCIAL CONTRACTS AND THEIR IMPACT - AMIRULLAYEV, Shodiyor (YURIST AXBOROTNOMASI, 2025)
Economic sanctions represent one of the most influential external factors shaping business operations in sanctioned countries. Companies engaged in cross-border trade must not only adjust their business strategies but also carefully manage the legal risks associated with sanctions compliance. These restrictions often lead to the adoption of improved internal procedures, standardized documentation, and increased implementation costs, all of which significantly affect contractual relations. In this environment, precontractual and contractual measures take on heightened importance. Businesses must conduct thorough due diligence, assess counterparties for compliance risks, and include tailored contractual provisions, such as sanctions clauses, warranties, and termination rights, to address potential disruptions. The inclusion of such provisions ensures that parties are prepared for changes in the sanctions regime, minimizing liability and safeguarding performance. Ultimately, sanctions transform how contracts are negotiated, drafted, and enforced, requiring businesses to balance legal obligations with commercial interests. This essay analyzes the legal impact of foreign economic sanctions on contracts, with particular attention to their influence on commercial agreements in international trade.